Hand osteoarthritis: diagnosis, pathogenesis, treatment - R. M. Balabanova; A. V. Smirnov; D. M. Kudinsky; L. I. Alekseeva (Современная ревматология)
Due to the development of synovitis, early-stage hand osteoarthritis (HOA) mimics hand joint injury in rheumatoid arthritis (RA). However, the topography of synovitis is diverse in these diseases:  distal interphalangeal and thumb joints are involved in the process in HOA. In the latter, tests are negative for immunological markers  (anti-cyclic citrullinated peptide antibodies), which is typical of RA.  The differences between HOA and RA are prominent, as evidenced  by hand X-rays and magnetic resonance imaging. Investigations  suggest that cytokine profile imbalance is implicated in the  pathogenesis of osteoarthritis, which brings it closer to RA. However, therapy for HOA has not been practically developed; there are only a few works on the use of disease-modifying antirheumatic drugs and  biological agents in these patients. It is necessary to work out Russian guidelines for the treatment of HOA.